PELAKSANAAN PELAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI RUMAH SAKIT UMUM ARIFIN ACHMAD PROVINSI RIAU TAHUN 2018 - Edo Rizkia Putra; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The objectives expected to be achieved through this research are to find out 1) Implementation of services of the Social Security Organizing Agency (BPJS) at Arifin Achmad General Hospital, Riau Province. 2) Obstacles in the implementation of the services of the Social Security Organizing Agency (BPJS) at Arifin Achmad General Hospital in Riau Province.The approach used in this study is a descriptive research approach with a qualitative type. The study was conducted at Arifin Achmad Hospital in Riau Province, located on Jalan Diponegoro No 2 Pekanbaru in December 2018 to February 2019. The technique of collecting data using interviews. Data analysis uses data reduction data presentation and conclusion drawing.Several things that became the conclusion of the study were 1) The implementation of BPJS Health services at Arifin Achmad Hospital was already underway. Arifin Ahmad Regional Hospital as a BPJS Health partner has carried out its obligations, namely to comply with all requirements specified in the MoU or Cooperation Agreement (SPK). Timely reporting of claims, and ICP following INA-CBGs in the service of patients participating in BPJS Health. The patient feels dissatisfied with health services. This BPJS Health policy does not get a positive response from Arifin Ahmad General Hospital, this is related to the income from the 2018 BPJS Health deficit. 2) Obstacles in the implementation of BPJS services at Arifin Achmad Hospital in Riau Province include income or revenue deficits, limitations on some provisions, and delay in issuing Patient Elegibility Letters (SEP) for BPJS Health participants. Keywords: Service Delivery, BPJS, RSUD